Effects of exogenous GA3 and warm water on dormancy breaking germination characteristics of Eucommia ulmoides - Ning WANG; Shanshan XU (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2023)
Seeds of the plant Eucommia ulmoides Oliver, have prominent dormant characteristics. In the present study, seed dormancy and germination of E. ulmoides were investigated by treating them with exogenous GA3 and different water temperatures. The results revealed that exogenous GA3 and warm water soaking treatments were beneficial to the dormancy breaking and germination of seeds. The germination rate of seeds treated with 50℃ water was 84.67%. In comparison, the seeds treated with 300 mg·L-1 GA3 had only a germination rate of 45%. This low germination rate resulted probably due to the low temperature of the GA3 solution. Another important reason is the presence of eucommia gum in the seed coat of E. ulmoides which hinders the germination process. During germination, the SOD activity in the seeds treated with GA3 (300 mg·L-1) and warm water (50 °C) increased significantly. Increased SOD activity reduced the degree of oxidative damage of the plasma membrane and resulted a continuous decrease in TBARS content. Thereby, the seeds were prompted to develop in a direction conducive to germination. In addition, GA3 (300 mg·L-1) and warm water (50℃) treatments increased the content of endogenous GA3, IAA, and ZR in the seeds, and decreased the content of endogenous ABA. This had resulted significantly higher ratios of GA3/ABA, IAA/ABA and ZR/ABA than those ratios of distilled water (room temperature) treated plants. In short, 50 °C warm water treatment has a more marked germination promoting effect on E. ulmoides seeds.